Specification. Harmonized system of quality assessment for electronic components: sectional specification for polycarbonatedielectric capacitors and polyethylene terephthalate dielectric capacitors for d.c. use. Polyester film capacitors with metal foil electrodes Part 1, (31st January 1980) - British Standards Institution,
No abstract available